Anti-inflammatory and nitric oxide-inhibiting properties of granulocyte colony-stimulating factor. - Hoffmann Georg; Schobersberger Wolfgang (Acta Pharmacologica Sinica, 2016)
A proposed scheme between the possible interactions of pro- and anti-inflammatory cytokines, NO and G-CSF during severe inflammation/infection is presented. Taken together, these data indicate that G-CSF exhibits anti-inflammatory properties which may prove to be beneficial in situations associated with an increased activity of the cellular immune system. Since the suppressive effects of G-CSF on the production of pro-inflammatory mediators like TNF-alpha and nitric oxide are most likely neither cell type nor tissue specific, it is conceivable that NO release induced by pro-inflammatory mediators can be reduced by G-CSF in various organ systems and in different forms of shock. In this context, G-CSF might represent a counterregulatory mechanism directed against a downstream oriented inflammatory response to infection. Therefore, the investigation of G-CSF in the prophylaxis of nonneutropenic infections, sepsis, and other severe inflammatory disorders seems reasonable.